Fiber-optic rudder position sensor for unmanned vessels. Issue 2 (November 2020) - Sedova, N; Sedov, V; Bazhenov, R; Povkh, I; Alekseeva, L; Korosteleva, I
Abstract: The paper presents the results of a study on the design of the rudder position sensor of a steering vessel, in which an optic fiber is a sensitive element and a data transmission line. A design of a sensitive element based on the effect of bending modulation of light transmission of an optic fiber is proposed, and a mathematical expression is obtained in ray equivalence, which describes the behavior of the sensitive element. The prototypes of the sensitive element and the laboratory setup have been developed, numerical modeling has been carried out, and experimental results have been obtained showing the potential use of the proposed approach for this class of problems.